Subjectivity of the Anomalous Sense of Self Is Represented in Gray Matter Volume in the Brain - Kanayama, Noriaki; Asai, Tomohisa; Nakao, Takashi; Makita, Kai; Kozuma, Ryutaro; Uyama, Takuto; Yamane, Toshiyuki; Kadota, Hiroshi; Yamawaki, Shigeto (Frontiers in Human Neuroscience, 2017)
The self includes complicated and heterogeneous functions. Researchers have divided the self into three distinct functions called “agency,” “ownership,” and “narrative self.” These correspond to psychiatric symptoms, behavioral characteristics, and neural responses, but their relationship with brain structure is unclear. This study examined the relationship between the subjectivity of self-related malfunctions and brain structure in terms of gray matter (GM) volume in 96 healthy people. They completed a recently developed self-reported questionnaire called the Embodied Sense of Self Scale (ESSS) that measures self-related malfunctions. The ESSS has three subscales reflecting the three distinct functions of the self. We also determined the participants’ brain structures using magnetic resonance imaging and voxel-based morphometry. Multiple regression analysis revealed a significant negative correlation between ownership malfunction and the insular cortex GM volume. A relationship with brain structure could thus only be confirmed for the ESSS “ownership” subscale. This finding suggests that distinct brain structures feel ownership and that the ESSS could partly screen for distinct brain structures.